Nilai Budaya dalam Cerita Rakyat Masyarakat Wakatobi sebagai Media Pendidikan Multikultural - Alias Alias; La Ode Muhammad Detif Rahim (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This study aims to explain and describe the cultural values in Wakatobi folklore books as a medium for multicultural education in the Wakatobi community in Kendari City. Folklore in Indonesia is an important part of the noble culture of oral literature of the community, but it is still rarely the object of study from the perspective of multicultural education. A qualitative approach was used in this research, with a qualitative descriptive analysis method using discourse analysis techniques on folklore texts. Data collection was conducted through reading, note-taking, and interviews. The results showed that Wakatobi folklore books contain five cultural values that can act as a medium for multicultural education in Kendari. These values include keeping promises to create discipline and trust, solidarity and brotherhood to form bonds of unity, never giving up disciplined and responsible characteristics, deliberation to unite social differences, and mutual cooperation to form family relationships, kinship, and unity. This research provides insight into the importance of folklore as a means of multicultural education to strengthen harmonious social life in Kendari.